Effect of Electrical Stimulation on PC12 Cells Cultured in Different Hydrogels: Basis for the Development of Biomaterials in Peripheral Nerve Tissue Engineering - Yusser Olguín; Mónica Selva; Diego Benavente; Nicole Orellana; Ivan Montenegro; Alejandro Madrid; Diego Jaramillo-Pinto; María Carolina Otero; Tomas P. Corrales; Cristian A. Acevedo (MDPI AG, 2023)
Extensive damage to peripheral nerves is a health problem with few therapeutic alternatives. In this context, the development of tissue engineering seeks to obtain materials that can help recreate environments conducive to cellular development and functional repair of peripheral nerves. Different hydrogels have been studied and presented as alternatives for future treatments to emulate the morphological characteristics of nerves. Along with this, other research proposes the need to incorporate electrical stimuli into treatments as agents that promote cell growth and differentiation; however, no precedent correlates the simultaneous effects of the types of hydrogel and electrical stimuli. This research evaluates the neural differentiation of PC12 cells, relating the effect of collagen, alginate, GelMA, and PEGDA hydrogels with electrical stimulation modulated in four different ways. Our results show significant correlations for different cultivation conditions. Electrical stimuli significantly increase neural differentiation for specific experimental conditions dependent on electrical frequency, not voltage. These backgrounds allow new material treatment schemes to be formulated through electrical stimulation in peripheral nerve tissue engineering.